Necessary nonsense : aesthetics, history, neurology, psychology - Massey, Irving (The Ohio State University Press, 2018)
"This book explores the cognitive possibilities of nonsense, literary and philosophical--ranging from Immanuel Kant to Lewis Carol, from examinations of Asperger's Syndrome to the waking state--and demonstrates that there is an element of nonsense, or stage of nonsense, in the normal course of thought"-- Provided by publisher
Keywords: Nonsense literature -- History and criticism.; Literature -- Aesthetics.; Literature -- Psychology.; Littérature nonsensique -- Histoire et critique.; Littérature -- Esthétique.; Littérature -- Psychologie.; BIOGRAPHY & AUTOBIOGRAPHY -- Literary.; LITERARY CRITICISM -- General.; Literature -- Aesthetics; Literature -- Psychology; Nonsense literature; Electronic books.; Criticism, interpretation, etc.